Urban Nomadism: Studying the Changing Culture of Remote Workers - Tavo, Koppel; Rasmus, Romann; Heikki, Vana (Cognitionis Civitatis et Politicae, 2024)
The development of digital technology and the internet has enabled the emergence of urban nomadism, where remote workers can work from anywhere without being tied to a specific physical location. This phenomenon is gaining popularity among young professionals seeking flexibility and work-life balance. However, these changes carry significant cultural implications for remote workers and the communities in which they live. This study examines cultural changes among remote workers who adopt an urban nomad lifestyle. The main focus of research is to understand how these lifestyles affect social interactions, cultural identity, and community dynamics. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with 20 remote workers who had adopted an urban nomadism lifestyle for over a year. In addition, participatory observations were conducted to observe these workers' social interactions and daily activities at various work sites. The results show that urban nomadism has changed how remote workers interact with their surroundings. Flexibility in work provides greater freedom but also creates challenges in building stable and deep social relationships. The cultural identity of remote workers is becoming more dynamic and multicultural, but there is also a feeling of alienation from the local community. This study concludes that urban nomadism brings about complex cultural changes for remote workers. While this lifestyle offers freedom and flexibility, there is a need for better strategies for building social connections and cultural integration. Remote workers and local communities must find effective ways to create mutually beneficial relationships and support social sustainability. Research Results: The results show that urban nomadism has changed how remote workers interact with their surroundings. Flexibility in work provides greater freedom but also creates challenges in building stable and deep social relationships. The cultural identity of remote workers is becoming more dynamic and multicultural, but there is also a feeling of alienation from the local community. Research Conclusion: This study concludes that urban nomadism brings about complex cultural changes for remote workers. While this lifestyle offers freedom and flexibility, there is a need for better strategies for building social connections and cultural integration. Remote workers and local communities must find effective ways to create mutually beneficial relationships and support social sustainability.